Memanfaatkan Analisis Kritis untuk Menelaah Gagasan Green Law Daerah untuk Pengelolaan dan Perlindungan Lingkungan Hidup Indonesia - Yudha Yosephine Tambunan; Aditia Sinaga; Muhammad Rafli Firdausi (Lembaga Pengembangan Kinerja Dosen, 2024)
In today's criminal justice discourse, restorative justice has gained traction. A restorative justice system has been included into the institutional policy of several law enforcement agencies. Additionally, it is included in the 2020–2024 National Medium-Term Development Plan (RPJMN). Since restorative justice is beneficial to and compatible with environmental conservation, it has also been developed in the field of environmental law. In light of this, the present study examines restorative justice as a broad idea within the context of Indonesian environmental legislation. This paper also highlights issues and considers critically whether the normative juridical approach of restorative justice may be used to address environmental crimes.